Optimizing Dependent Variables and Multi-Responses Regression Model Development - Nawzad. M. Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
This study is concerned as an extension and development of the results for a previous study which was done by the researcher, recommended to optimize the response variables for the (fitted multi-responses regression model, MRRM). This is tried to be done in this study, by building a linear programming systems for each response separately which produced in (MRRM), and solving these systems using linear programming procedure solution methodology named by (Simplex Method). In order to build these systems one can put each response (dependent variable) as an (objective) variable that required optimizing, and the independent variables (explanatory variables) are concerned as inputs to construct and building the (constraints). Then after solving these systems, it’s able to determine the optimal (maximum value for the objectives), and the values of inputs (independent variables), which maximize the objectives.